Rock Physics Modeling Assisted Reservoir Properties Prediction: Case Study in Malay Basin - Abbas Babasafari, Amir; Ghosh, Deva; M. A. Salim, Ahmed; Y. Moussavi Alashloo, S (International Journal of Engineering and Technology, 2018)
Shear velocity log is not measured at all wells in oil and gas fields, thus rock physics modeling plays an important role to predict this type of log. Therefore, seismic pre stack inversion is performed and elastic properties are estimated more accurately. Subsequently, a robust Petro-Elastic relationship arising from rock physics model leads to far more precise prediction of petrophysical properties. The more accurate rock physics modeling results in less uncertainty of reservoir modeling. Therefore, a valid rock physics model is intended to be built. For a better understanding of reservoir properties prediction, first of all rock physics modeling for each identified litho-facies classes should be performed separately through well log analysis.Â Â